2011
DOI: 10.3727/154427212x13369577826889
|View full text |Cite
|
Sign up to set email alerts
|

“It's a challenge, It's hard to get a wave”: the Impact of constraInts on women surf tourIsts

Abstract: This article aims to explore active female surfers' constraints associated with surf tourism. A qualitative, interpretive research paradigm informed by feminist perspectives was utilized. Twenty female surf tourists were interviewed in an effort to address the study's objectives. Semistructured in-depth interviews were the main data collection method, allowing women to freely speak about their experiences. Analysis of these interviews revealed a range of personal, sociocultural, and practical constraints, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…encountering localism and lack of travel companions) as well as practical constraints such as managing logistics and limited finances. Whereas many studies have focused on constraints as something negative, Fendt and Wilson (2012) found that female surfers actually valued moving past constraints and felt that this enhanced their surfing experience, even more than if no constraints were present. When a person has to struggle to overcome a mental or physical challenge within reach, eudaimonic feelings occur with a sense of psychological well-being (Moen & Vittersø, 2015;Ryan & Deci, 2001).…”
Section: Constraints In Leisure and Tourismmentioning
confidence: 92%
See 3 more Smart Citations
“…encountering localism and lack of travel companions) as well as practical constraints such as managing logistics and limited finances. Whereas many studies have focused on constraints as something negative, Fendt and Wilson (2012) found that female surfers actually valued moving past constraints and felt that this enhanced their surfing experience, even more than if no constraints were present. When a person has to struggle to overcome a mental or physical challenge within reach, eudaimonic feelings occur with a sense of psychological well-being (Moen & Vittersø, 2015;Ryan & Deci, 2001).…”
Section: Constraints In Leisure and Tourismmentioning
confidence: 92%
“…The results showed that intrapersonal constraints are demotivating for individuals, whereas structural and interpersonal constraints showed no relationship to motivation (Alexandris et al, 2002). Motivation has also been connected to 13 participation in the adventure activity of surfing in that constraints are less powerful the higher the motivation for participation (Fendt & Wilson, 2012), proving the connection between personality and participation.…”
Section: Personalitymentioning
confidence: 96%
See 2 more Smart Citations
“…In studies of entrepreneurship Max and Ballereau (2013) argue for more attention to female entrepreneurs, who are the object of skewed underrepresentation in the mass media in that they are depicted as women, whereas men are depicted as entrepreneurs. Fendt and Wilson (2012) looked into female surfers constraints, pinpointing that personal, sociocultural, and practical constraints where all felt among the informants. They also suggested that "traditional societal perceptions of females belonging to the domestic sphere" and that "surfing is still a male oriented leisure activity" is partly the reason why women feel disadvantaged in the surf due to their gender (Fendt & Wilson, 2012, p. 345).…”
Section: Gendered Domainsmentioning
confidence: 99%